MODERN MODELS OF EDUCATIONAL PROCESS ORGANIZATION IN HIGHER EDUCATION INSTITUTIONS - Artiqova Karomat Kamoldjonovna (Scholar Express Journal, 2023)
Development is an ongoing process with a specific goal in mind. There are certain rules for this process: the goal-orientedness of education, the humanitarian and democratic rule of education, the rule of priority of national and universal values in education, the rule of consistency, systematicity, unity and continuity of educational effects, and others.
Keywords: Education; patriotism; consistency